Entrepreneurship Education Learning Oriented To Develop Entrepreneurial Creativityshi High School Students Based On Project Based Learning - Juanda, Anda; Ali, Mohammad; Azizi, Azizi; Anshory, Yoyo Zakaria; Fathurohman, Oman (Ridwan Institute, 2025)
Learning entrepreneurship education for creative children of Gen Z age in high school as a step to prepare them to become entrepreneurship through entrepreneurship education learning activities. Emphasis on entrepreneurial education for creative children on handicraft products. The research approach is oriented to the philosophy of phenomenology with qualitative methods. The research sample used purposive sampling. Inductive data collection techniques: (1) interviews (2) observation and (3) documentation. Research data analysis: (1) data reduction, (2) data display, (3) (4) verification. Data sources include: (1) primary data and (2) secondary data. The primary data are grade XI students, and secondary data: teachers, principals and school administrative staff. The phenomena of the research explain that learning occurs in teacher-student dialogue and there is a transformation of changes in student learning, such as: students are able to make creative products, collaborative learning between students, group learning, independent, critical thinking, focusing on problem solving, making creative products in the form of crafts according to the needs of the community. The Project-based Learning learning model contributes to the development of entrepreneurial creativity in student entrepreneurship education learning.